Single vdta-based three-input singleoutput universal filter - Channumsin, Orapin; Tangsrirat, Worapong (My University, 2017)
A voltage-mode universal biquadratic filter with three input terminals and a single output terminal is presented which comprises of only one voltage differencing transconductance amplifier (VDTA), one grounded resistor and two capacitors. It employs a canonical number of active and passive elements, and can simultaneously realize lowpass, bandpass, highpass, bandstop and allpass responses with interconnection of relevant input voltages. The presented filter configuration also has low active and passive component sensitivities along with orthogonally adjustable natural angular frequency (ωo ) and the quality factor (Q). Simulation results which are accomplished with PSPICE program confirm the theory.
Keywords: Electronically tunable; Universal filter; Voltage differencing transconductance amplifier (VDTA); Voltage-mode circuit